Determining the hydrological functioning of the palmiet wetlands in the Eastern and Western Cape South Africa - Smith, Caitlin (Rhodes University, Faculty of Science, Institute for Water Research, 2019)
Wetlands provide a range of supporting, regulating and provisioning ecosystem services, including hydrological benefits such as flood attenuation and sustaining base flows. Despite their value, wetlands are one of the most vulnerable ecosystems in South Africa. Palmiet wetlands in the Eastern and Western Cape are particularly threatened. Palmiet (Prionium serratum) is a robust perennial plant that is endemic to wetlands and rivers located in the sandstones and quartzites of the Table Mountain Group (TMG), in the Eastern and Western Cape as well as the Natal Group sandstones in KwaZulu-Natal. Palmiet is described as an ecosystem engineer because of its ability to alter its environment and create large valley-bottom wetlands. The Krom River is an important water source for the city of Port Elizabeth and there has been a decline in palmiet wetlands along the Krom River as a result of alien vegetation invasion, agricultural activity, and gully erosion. Working for Water has been clearing alien vegetation and Working for Wetlands has been installing rehabilitation structures in the Krom River catchment for a number of years. There are, however, serious knowledge gaps in the understanding of palmiet wetland structure and function, particularly in respect of the hydrological functioning of these wetland systems. The aim of this study was to investigate the hydrology (surface and groundwater) behind these wetland systems. The investigation focussed on small-scale dynamics of the palmiet wetland system in order to increase general understanding of the surface water and groundwater processes of these wetland systems. Field work was concentrated on the Kompanjiesdrif and Krugersland palmiet wetlands in the upper K90A Krom River catchment. The investigation involved the installation of piezometers, water quality and stable isotope sampling and analysis, an Electrical Resistivity Tomography survey, and hydrological and mixing cell modelling. The results of the investigation indicate that the hydrological functioning of palmiet wetlands is closely linked with high sub-surface discharges typically associated with TMG aquifers. It is proposed that the palmiet wetlands are sustained by significant amounts of sub-surface water (both groundwater and interflow) moving through preferential flow paths in the alluvial fans and tributaries, which are in turn sustained by groundwater discharge from the surrounding sandstones and quartzites of the Nardouw Sub-group and Peninsula Formation. The palmiet wetlands clearly retain a significant amount of water, leading to the maintenance of prolonged flows, and a larger baseflow. However, it is hypothesised that the occurrence of palmiet as the dominant species in these wetlands is due to the sustained low flows related to catchment geology and high hydrological connectivity between the catchment and the wetland that is enabled by flow paths that allow the free flow of water from the catchment to the wetland. It is further proposed that palmiet is possibly more reliant on a consistent water supply for its existence and survival than it is on acidic nutrient-poor water and soils as stated by other authors.
Keywords: Wetlands -- South Africa -- Eastern Cape; Wetland ecology -- South Africa -- Eastern Cape; Wetland management -- South Africa -- Eastern Cape; Prioniaceae -- South Africa -- Eastern Cape; Prionium serratum -- South Africa -- Eastern Cape